Eksistensi Istri-Istri Rasulullah Dalam Periwayatan Hadis: The Existence of the Prophet's Wives in the Hadith Narration - Anwar, Latifah (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2023)
At the beginning of the spread and development of Islam, the intensity of women's involvement in the transmission of hadith was relatively high, although it could not be compared to the role played by male narrators. The search for and transmission of hadith, both by male and female narrators, was very high during the time of the Prophet Muhammad. In the narration of hadiths, it is not only male friends who mostly narrate hadiths but also those female companion who were w the wives of the Prophet Muhammad. The women who made a major contribution to the transmission of hadith were the wives of the Prophet, although there were also many women outside the Prophet's family circle. In this article, the authors examine the role of the wives of the Prophet in the narration of hadith. Among the twelve wives of the Prophet Muhammad, there were 9 Umm al-Mu'minin who played a role in the narration of hadith, namely Sawdah bintu Zam'ah, 'Aishah bintu Abi Bakr al-Shiddiq, Hafshah bintu 'Umar bin Khaththab, Umm Salamah, Zaynab bintu Jahsh, Juwayriyah bintu al-ha>rits, Umm Habibah, Shafiyah bintu H}uyay, and Maymunah bintu al-Harits. Some of them, are known as the most hadith transmitters, namely 'Aishah. Meanwhile, the three other wives of the Prophet, such as; Khadijah bintu Khuwaylid, Zaynab bintu Khuzaymah and Mauriyah al-Qibt}iyyah, didn’t have a single hadith that they narrated.